Synthesis of bismuth titanate by the urea method - Anilkumar, Mettu; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple urea precipitation route was adopted for the preparation of bismuth titanate (Bi4Ti3O12) powders. Stoichiometric quantities of BiCl3 and TiOCl2 were mixed with the required amount of urea (the ratio of total metal cations to urea is five), and the mixture was heated on a water bath. This leads to the formation of precipitate, which was decomposed at 973 K. The formation of bismuth titanate was observed on calcining powders at 973 K by X-ray diffraction studies. The average particle size is found to be 100 nm by microscopy. The room temperature dielectric constant is found to be 150 at 1 kHz. The hysteresis loop parameters were also obtained by home-built Sawer-Tower circuit. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; dielectric properties; ferroelectricity; X-ray diffraction